Forms of the Real or Under What Circum-stances Does the Word Make us See? - Ferreira de Almeida, María Cándida (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This paper presents the problem of creative processes involved in passing from one art to another. To bring forward this reflection, it was selected the problem of the configuration from the real, such as it was carried out in painting, photography or film and then to understand its appropriation by using the literary speech. The purpose of this paper is to make comprehensible the operations that support a realistic representation, conceived as a rhetorical procedure expressed under the evidence, and still, it interpellates a realistic visual experience exclusive by means of the written word. Handling with the written word’s boundaries, we try to prove the thesis in this paper, not only in the prose, traditional locus of realism, but also as in poetry